Internalization of Islamic Religious Education Values Based on Religious Moderation: A Study on IPNU IPPNU PAC Organization in Seputih Mataram District Central Lampung Regency - Dimas Misbakhul Fajar; Muhammad Yusuf; Habib Sulthon Asnawi (Assyfa Journal of Islamic Studies, 2025)
This study aims to explore and analyze the internalization of Islamic Religious Education (PAI) values based on religious moderation within the IPNU and IPPNU organizations at the sub-district level (PAC) of Seputih Mataram, Central Lampung Regency. The research employs a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation involving organizational leaders, active members, and community figures. The findings reveal five core values of religious moderation internalized: commitment to nationality, tolerance, anti-violence, accommodation to local culture, and amar ma'ruf nahi munkar (enjoining good and forbidding evil). These values are institutionalized through three integrated pathways: formal organizational activities (Makesta, Lakmud, Lakut, routine recitations, and leadership training), role modeling by organizational leaders, and organizational culture (deliberation, collective work, tahlilan, yasinan, and national activities). The contribution of these values manifests in strengthened member character, enhanced tolerance and cooperation, violence and conflict prevention, and adaptation to local culture. The implications are evident in members' behavior: reinforced national commitment, tolerant attitudes, conflict management skills, and appreciation of local culture. This research contributes theoretically to the literature on Islamic education based on religious moderation and practically provides recommendations for student development programs at the village level, demonstrating that IPNU and IPPNU serve as effective mediums for character education that is moderate, contextual, and relevant to the social and cultural needs of local communities.